Adaptation of Mixed Gender Unit Members to Working Environment - Marček, Jan; Šaranović, Jovanka (NBP. Nauka, bezbednosti, policija, 2022)
Adaptation is a process of changing a person in accordance with characteristics and requirements of the social environment. It can be social, psychological and physiological. The adaptation of members of the mixed gender military units (officers, non-commissioned officers and professional soldiers) to all specifics of military organization (manner and organization of work, restrictions, psychological and physical strains, etc.) is certainly a specific process, especially in relation to other organizations. Accordingly, the objective of this part of the research was to determine the extent to which members of mixed gender units are adapted to working conditions in military organization and what kind of a relationship between individual characteristics of respondents (sex, age and years of service) and their evaluation of adaptability to working conditions in military organization is. The research has used descriptive Research method, using the Questionnaire on the professional efficiency of mixed gender units, whose integral part is a five-point Likert-type scale for assessing the adaptability to working conditions in military organization. Data processing, in addition to descriptive analysis, has been performed using Chi-square test, variance analysis and factor analysis. The obtained results have wider implications because they indicate the adaptation of a person to the work environment, which in some aspects is similar to the military environment.